Magnetic resonance imaging of oxygen microbubbles. Issue 5 (21st August 2019) - Thompson, Elinor; Smart, Sean; Kinchesh, Paul; Bulte, Daniel; Stride, Eleanor
Abstract : Oxygen loaded microbubbles are being investigated as a means of reducing tumour hypoxia in order to improve response to cancer therapy. To optimise this approach, it is desirable to be able to measure changes in tissue oxygenation in real‐time during treatment. In this study, the feasibility of using magnetic resonance imaging (MRI) for this purpose was investigated. Longitudinal relaxation time (T1) measurements were made in simple hydrogel phantoms containing two different concentrations of oxygen microbubbles. T1 was found to be unaffected by the presence of oxygen microbubbles at either concentration. Upon application of ultrasound to destroy the microbubbles, however, a statistically significant reduction in T1 was seen for the higher microbubble concentration. Further work is needed to assess the influence of physiological conditions upon the measurements, but these preliminary results suggest that MRI could provide a method for quantifying the changes in tissue oxygenation produced by microbubbles during therapy.